Assessing the economic indicators that influence the residential property price in Kuala Lumpur - Ahmad Shukri, Ahmad Syahmi Haziq (2025)
In recent years, the increase in residential property prices has become a growing concern globally. Malaysia is no exception, with housing prices rising faster than household income, especially in urban areas such as Kuala Lumpur. This imbalance has led to significant affordability issues. While the topic has received attention, limited research has been conducted on the relationship between macroeconomic indicators and residential property prices in Kuala Lumpur over an extended period. This study aims to investigate the relationship between selected economic indicators, namely inflation, interest rate, gross domestic product (GDP), unemployment rate, and the Kuala Lumpur Housing Price Index (HPI) from 2014 to 2024. Using a quantitative approach, secondary data were collected from Bank Negara Malaysia (BNM), the Department of Statistics Malaysia (DOSM), and the National Property Information Centre (NAPIC). Multiple Regression Analysis (MRA) was employed to determine the extent to which these indicators influence housing prices. The results reveal that inflation and interest rates have a significant positive effect on HPI, while GDP shows a significant negative relationship. Unemployment rate was excluded from the model due to multicollinearity issues. This study provides valuable insights into how macroeconomic conditions shape the housing market in Kuala Lumpur. The findings are expected to assist policymakers, real estate professionals, and investors in making more informed decisions and developing strategies to improve housing affordability and market stability.